Development of [124/125I]IAZA as a New Proteinopathy Imaging Agent for Alzheimer’s Disease - Thrisha T. Reddy; Michael H. Iguban; Lusine L. Melkonyan; Jasmine Shergill; Christopher Liang; Jogeshwar Mukherjee (Molecules, 2023)
Radioiodinated imaging agents for Aβ amyloid plaque imaging in Alzheimer’s disease (AD) patients have not been actively pursued. Our previous studies employed the “diaza” derivatives [11C]TAZA and [18F]flotaza in order to develop successful positron emission tomography (PET) imaging agents for Aβ plaques. There is a need for radioiodinated imaging agents for Aβ plaques for single photon emission computed tomography (SPECT) and PET imaging. We report our findings on the preparation of [124/125I]IAZA, a “diaza” analog of [11C]TAZA and [18F]flotaza, and the evaluation of binding to Aβ plaques in the postmortem human AD brain. The binding affinity of IAZA for Aβ plaques was Ki = 10.9 nM with weak binding affinity for neurofibrillary tangles (Ki = 3.71 μM). Both [125I]IAZA and [124I]IAZA were produced in >25% radiochemical yield and >90% radiochemical purity. In vitro binding of [125I]IAZA and [124I]IAZA in postmortem human AD brains was higher in gray matter containing Aβ plaques compared to white matter (ratio of gray to white matter was >7). Anti-Aβ immunostaining strongly correlated with [124/125I]IAZA in postmortem AD human brains. The binding of [124/125I]IAZA in postmortem human AD brains was displaced by the known Aβ plaque imaging agents. Thus, radiolabeled [124/123I]IAZA may potentially be a useful PET or SPECT radioligand for Aβ plaques in brain imaging studies.